1984
DOI: 10.1111/j.1471-4159.1984.tb06099.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Jimpy Mutation on Expression of Myelin Proteins in Heterozygous and Hemizygous Mouse Brain

Abstract: The levels of myelin basic protein, proteolipid protein, and 2',3'-cyclic nucleotide 3'-phosphohydrolase (EC 3.1.4.37) in cerebral hemispheres of wild-type, heterozygous jp/+, and hemizygous jp/Y mice of different ages were determined by radioimmunoassay and immunoblotting. In jp/Y brain the level of myelin basic protein was 8% that of wild-type at all ages. All forms of the protein were reduced although the 21.5K Mr form was relatively spared at early ages compared to the 18.5K, 17K, and 14K Mr forms. The lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
30
1

Year Published

1986
1986
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 33 publications
6
30
1
Order By: Relevance
“…This is consistent with other studies (21,35,38) indicating that in Tajp heterozygous females, the amounts of these proteins or their mRNAs are reduced. Sorg et al (38) reported an approximate 25% reduction in the amount of MBP mRNA in heterozygous females.…”
Section: Discussionsupporting
confidence: 82%
“…This is consistent with other studies (21,35,38) indicating that in Tajp heterozygous females, the amounts of these proteins or their mRNAs are reduced. Sorg et al (38) reported an approximate 25% reduction in the amount of MBP mRNA in heterozygous females.…”
Section: Discussionsupporting
confidence: 82%
“…Differences between jimpy and wild-type PLP mRNA demonstrated by Sl-nuclease protection experiments (27) are also approximately consistent with the size and position of the deletion described here. A primary defect in the PLP gene in jimpy mice is consistent with the severe reduction in PLP concentration in jimpy brains (6)(7)(8)(9) and with ultrastructural (28,29), biochemical (30), and in vitro studies (31) that indicate that the primary genetic defect is expressed in oligodendrocytes. The significantly reduced mRNA levels in the mutant (Fig.…”
Section: Discussionmentioning
confidence: 75%
“…4). Myelin proteolipid protein (PLP), or lipophilin, is of particular relevance to the jimpy mutation because it is expressed specifically in the central nervous system (5) and is one of the most severely reduced myelin constituents of jimpy brains (6)(7)(8)(9). Furthermore, the gene for PLP has been mapped to the X chromosome in both man and mouse (10).…”
mentioning
confidence: 99%
“…The hypomyelination injimpy mice is more severe than in shiverer and appears to be associated with a partial deletion of the coding region of PLP mRNA due to an aberrant splicing of the primary gene transcript (3)(4)(5)(6). PLP, an intrinsic membrane protein thought to play a role in compaction of the extracellular leaflets of CNS myelin, is absent or dramatically reduced in jimpy mice (7)(8)(9).…”
mentioning
confidence: 99%